Application of bentonite grout in AKARPILES / Chun-Lan Lim and Chee-Ming Chan - Chun, Lan Lim; Chee, Ming Chan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
AKARPILES is an innovative solution for slope stabilization with less environmental footprint. Grout is one of the key components in AKARPILES. This study focused on stabilizing surficial slope failure, which commonly occurred in Malaysia. There are many methods help to improve slope stability of slopes. The idea of AKARPILES was innovated from the function of the tree root system in slope stabilization. Grout was pumped in and discharged through the outlets on the piles, after the piles are installed on the slope and intercepting the slip plane. The grout had then filled the voids within the soil with random pattern. SKW mixture was used to simulate the soil slope. Trial mix of the grout was carried out to obtain the optimum mixing ratio of bentonite: cement: water. Cone penetration test (CPT) and vane shear test (VST) were conducted on the grout mixture in a different mix ratio to obtain the strength gained. Grout dispersion area by two different designs of AKARPILES were recorded and compared. The results were affected by the design of piles.